2007
DOI: 10.1016/j.jtcvs.2007.04.020
|View full text |Cite
|
Sign up to set email alerts
|

Aortic valve replacement with the Sorin Pericarbon Freedom stentless prosthesis: 7 years’ experience in 130 patients

Abstract: The Sorin Pericarbon Freedom stentless bioprosthesis provides good early and midterm results in terms of hemodynamic performance, survival, and freedom from valve-related complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 17 publications
2
10
0
Order By: Relevance
“…The haemodynamics of the FS bioprosthesis, in terms of transvalvular gradients and effective orifice areas indexed, have been shown to be at least as good as those of other routinely used stentless valves [2,12,13]. Moreover, it is interesting to note that, in our study, 24% of patients had a prosthesis size 21 or 19 and 61% a prosthesis size 23 or less.…”
Section: Discussionsupporting
confidence: 55%
“…The haemodynamics of the FS bioprosthesis, in terms of transvalvular gradients and effective orifice areas indexed, have been shown to be at least as good as those of other routinely used stentless valves [2,12,13]. Moreover, it is interesting to note that, in our study, 24% of patients had a prosthesis size 21 or 19 and 61% a prosthesis size 23 or less.…”
Section: Discussionsupporting
confidence: 55%
“…A bovine Sorin Pericarbon Freedom10 and an equine 3F heart valve11 are available in the market. These pericardial valves are flexible, easy to implant, and show an extremely good hemodynamic performance.…”
Section: Various Stentless Bioprostheses and Implantation Techniquementioning
confidence: 99%
“…22–30 Several studies showed an improved survival after stentless AVR, probably due to better hemodynamic performance and earlier LV mass regression compared with stented AVR 3138. However, there was a bias of operation age and nonrandomization.…”
Section: Long-term Outcomesmentioning
confidence: 99%
“…The haemodynamic performance of the Freedom Solo valve and other types of stentless valves has been well established, both in early and mid-term phases (23,24) . Although stentless valves initially had a similar technique of implantation as many other stentless or stented valves, the Sorin Pericarbon Freedom valve and Freedom Solo valve had an easier implantation technique involving 3 sutures or a single suture throughout the aortic annulus (8,9) .…”
Section: Discussionmentioning
confidence: 99%